PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA MATA PELAJARAN KONFIRMASI KEPUTUSAN PELANGGAN KELAS X PEMASARAN SMK BATIK 1 SURAKARTA TAHUN AJARAN 2014/2015 - Hamidah Fajrin; Soetarno Joyoatmojo; Sri Wahyuni (Department of Economics Education, Universitas Sebelas Maret, 2018)
The objective of this research is to improve the critical thinking ability and the learning achievement in Consumer-Based Decision Confirmation of the students in Grade X of Marketing Department of Vocational High School Batik 1 of Surakarta in Academic Year 2014/2015 through the application of the Cooperative Learning Model of the TPS type. This research used the classroom action research (CAR) with two cycles. The achievement of research shows that the cooperative learning model of the TPS type could improve the critical thinking ability and the learning achievement in the Consumer-Based Decision Confirmation subject matter of the students in Grade X of Marketing Department of Vocational High School Batik 1 of Surakarta in Academic Year as shown by the following: The critical thinking ability on the aspect of Focusing Problems increased as much as 29.03% (In Cycle I it was 64.52%, and in Cycle II it became 93.55%); the critical thinking ability on the aspect of Considering Sources or Theories increased as much as 32.26% (In Cycle I it was 58.06%, and in Cycle II it became 90.32%); the critical thinking ability on the aspect of Identifying Problems increased as much as 35.49% (In Cycle I it was 58.06%, and in Cycle II it became 93.55%); the critical thinking ability on the aspect of Giving Alternatives to Solve Problems increased as much as 32.25% (in Cycle I it was 54.84%, and in Cycle II it became 87.09%); the critical thinking ability on the aspect of Explaining Alternatives to Solve Problems increased as much as 32.26% (in Cycle I it was 51.61%, and in Cycle II it became 83.87%); and the critical thinking ability on the aspect of Drawing Conclusions increased as much as 22.58% ( in Cycle I it was 74.19%, and in Cycle II it became 96.77%). Furthermore, prior to the application of the cooperative learning model of the TPS type, class average score was 75.23 with learning completeness of 47%. Following the treatment, the score average score became 77 with the learning completeness of 74.2% in Cycle I and 83.38 with the learning completeness of 90.32% in Cycle II. Thus, the application of the cooperative learning model of the TPS type could improve the critical thinking ability and the learning achievement in the Consumer-Based Decision Confirmation subject matter.